(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The goal of the research is to prepare a proposed audit program that addresses the audit of long-term financial sustainability dimensions by external auditors and how auditing these dimensions affects strategic decisions. The research problem lies in the contemporary financial environment in which institutions deal with a variety of issues, including improving their investments and finding sources of financing. This is particularly evident in the case study sample represented by the Industrial Bank, where the bank relies heavily on a single source of income, which is interest paid in Iraqi currency, and its increasing dependence on deposits compared to its capital. Moreover, the bank’s use of electronic systems in banking operations is insufficient and lacks strategic planning based on long-term financial sustainability elements (revenues, services, debt).The external auditor plays a vital role in verifying the bank’s strategic plans, which include revenue diversification, expanding services, managing debt, and guiding bank management. The research results showed a lack of a strategic plan according to the dimensions of financial sustainability, investments in loss-making or inactive economic units, low return on investment compared to the size of the investment, and the absence of a marketing strategy along with insufficient marketing expenditures for its services. Based on the conclusions reached, the research recommended several measures, including the necessity of developing comprehensive plans based on a detailed analysis of the market, reviewing the bank’s investments to identify non-viable units, and reallocating funds to more profitable opportunities. It also suggested developing a comprehensive marketing strategy to better understand the market, thereby enhancing the bank’s image and increasing its attractiveness to customers.